Imidazole and beta-carotene photoprotection against photodynamic therapy evaluated by synchrotron infrared microscopy - Bosio, Gabriela Natalia (2018)
In order to better understand the role of β-carotene and imidazole on the Photodynamic Therapy (PDT) mechanism, synchrotron infrared microscopy was used to detect the associated intracellular biochemical modifications following the visible light irradiation of HeLa cells incubated with these compounds as typical hydrophobic and hydrophilic singlet oxygen quenchers, respectively. For this purpose, PDT was performed employing the hydrophilic sensitizer 5,10,15,20-Tetrakis (1-methyl-4-pyridinio) porphyrin tetra (p-toluenesulfonate), TMPyP, and the hydrophobic sensitizer 5-(4-Methoxycarboxyphenyl)-10,15,20-triphenyl-21H,23H–porphyrin. The single cell IR spectra of PDT-treated, PDT plus quencher-treated and control HeLa cells were recorded at the SOLEIL Synchrotron Infrared SMIS beamline targeting specifically the cell nucleus. Principal Component Analysis (PCA) was used to assess the IR spectral changes. PCA revealed that there is a frequency shift of the protein Amide I vibrational band for the assays with the TMPyP sensitizer, indicating changes in the protein secondary structures of the PDT-treated cancer cells compared to the controls. In addition, the scores in those cells treated with both quenchers appear to be similar to the controls indicating a photoprotective effect. Comparative experiments carried out with SKMEL-28 and HaCat cells showed non- significant photoprotective effects of β-carotene and imidazole.